Behavioural issues in environmental modelling – The missing perspective. (November 2015) - Hämäläinen, Raimo P.
Abstract: The paper aims to demonstrate the importance of behavioural issues in environmental modelling. These issues can relate both to the modeler and to the modelling process including the social interaction in the modelling team. The origins of behavioural effects can be in the cognitive and motivational biases or in the social systems created as well as in the visual and verbal communication strategies used. The possible occurrence of these phenomena in the context of environmental modelling is discussed and suggestions for research topics are provided. Highlights: Behavioural effects of the modeler and the modelling process need to be studied. Cognitive, motivational and social biases and communication effects are important. Modelers are also subject to other biases which must be considered. Modelers should recognize the possibility of strategic behavior of the participants. Modeler in the problem solving system must act with systems intelligence.